1980
DOI: 10.1111/j.1476-5381.1980.tb14559.x
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Adrenaline‐induced Hyperglycaemia in the Anaesthetized Cat by Continuous Infusion of Phentolamine and Propranolol

Abstract: 1 The effects of adrenoceptor blocking drugs on the metabolic responses to adrenaline infusion (I pg kg-I minm ') have been studied in the anaesthetized, fasted cat. 2 Propranolol, in doses (0.25 or 1 mg/kg) which prevented completely adrenaline-induced tachycardia, reduced but did not abolish adrenaline-induced hyperglycaemia.3 Phentolamine infusion, at a rate (15 pg kg-' min-' after a priming dose of 2.5 mg/kg) which reversed the pressor effect of adrenaline, reduced but did not abolish adrenaline-induced hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, the contribution of each component differs in different species and under different nutritional status (Al-Jibouri et al, 1980). Previous studies in humans and rats (Rizza, 1980, Al-Jibouri et al, 1980, Moratinos et al, 1986, Oyebola and Alada, 1993 have shown that activation of alpha, beta, or both alpha-and beta-adrenergic receptors are involved in adrenaline-induced hyperglycemia. There is limited information on the role of adrenergic receptors in the action of adrenaline on plasma lactate, liverand muscle glycogen in amphibians.This study investigated the effects of adrenaline on blood glucose, plasma lactate, liver and skeletal muscle glycogen and the role of adrenergic receptors in the common African toad bufo regularis.…”
mentioning
confidence: 95%
“…However, the contribution of each component differs in different species and under different nutritional status (Al-Jibouri et al, 1980). Previous studies in humans and rats (Rizza, 1980, Al-Jibouri et al, 1980, Moratinos et al, 1986, Oyebola and Alada, 1993 have shown that activation of alpha, beta, or both alpha-and beta-adrenergic receptors are involved in adrenaline-induced hyperglycemia. There is limited information on the role of adrenergic receptors in the action of adrenaline on plasma lactate, liverand muscle glycogen in amphibians.This study investigated the effects of adrenaline on blood glucose, plasma lactate, liver and skeletal muscle glycogen and the role of adrenergic receptors in the common African toad bufo regularis.…”
mentioning
confidence: 95%